2021
DOI: 10.1249/01.mss.0000762532.12313.2e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Fundamental Motor Skill Intervention on Body Composition Outcomes in Preschool Children

Abstract: METHODS:Parents or guardians of children with T1D (< 18 years) filled out an online survey. Anthropometric characteristics, PA, play and sport and sedentary time were collected before and after the introduction of restrictions. Moreover, we investigated the medical-related factors. RESULTS: a total of 280 children and adolescents (mean age was 11.8±3.3 years; 58.5% M) were included in the analysis. Before and after the introduction of restrictions, we reported a significant decline in participation in sport ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The interconnection of memory and motor development has also been observed in other studies, which have shown the effect of motor memory in action choice and in procedural learning. Thus, motor memory, considered an intrinsic property of the motor system, can impact not only motor behavior, depending on the constraints, but also higher cognitive functions [ 42 ]. Indeed, current theories on memory function consider that both declarative knowledge and procedural skills might be acquired based on sensorimotor interaction and interactive behavior [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interconnection of memory and motor development has also been observed in other studies, which have shown the effect of motor memory in action choice and in procedural learning. Thus, motor memory, considered an intrinsic property of the motor system, can impact not only motor behavior, depending on the constraints, but also higher cognitive functions [ 42 ]. Indeed, current theories on memory function consider that both declarative knowledge and procedural skills might be acquired based on sensorimotor interaction and interactive behavior [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%